2022
DOI: 10.3390/molecules27206874
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Antimicrobial and Anti-Biofilm Activity of Natural Compounds and Their Analogues against Staphylococcus aureus Isolates

Abstract: (1) Background: Staphylococcus aureus (S. aureus) is one of the most frequent causes of biofilm-associated infections. With the emergence of antibiotic-resistant, especially methicillin-resistant S. aureus (MRSA), there is an urgent need to discover novel inhibitory compounds against this clinically important pathogen. In this study, we evaluated the antimicrobial and anti-biofilm activity of 11 compounds, including phenyl propenes and phenolic aldehydes, eugenol, ferulic acid, sinapic acid, salicylaldehyde, v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…The susceptibility of E. coli isolates to the total extract and its isolated compounds was revealed by the agar well-diffusion method [ 78 ]. Briefly, after spreading the bacterial suspensions on the Muller–Hinton agar plates, cups were made, and the tested compounds, in dimethyl sulfoxide (DMSO) with concentrations of 1000 µg/mL, were poured into the cups.…”
Section: Methodsmentioning
confidence: 99%
“…The susceptibility of E. coli isolates to the total extract and its isolated compounds was revealed by the agar well-diffusion method [ 78 ]. Briefly, after spreading the bacterial suspensions on the Muller–Hinton agar plates, cups were made, and the tested compounds, in dimethyl sulfoxide (DMSO) with concentrations of 1000 µg/mL, were poured into the cups.…”
Section: Methodsmentioning
confidence: 99%
“…The relative gene expression of the treated isolates was compared to that of the untreated ones according to the 2 −∆∆Ct method [76]. Primers are exposed in Table S1 [77,78].…”
Section: Gene Expression Measurement Using Qrt-pcrmentioning
confidence: 99%
“…Recent studies have indicated that various natural compounds not only inhibit biofilm formation but also eradicate mature biofilm produced by several bacterial species, including S. aureus (Mastoor et al, 2022). Essential oils are mixtures of secondary metabolites obtained from plants, which can exert an antimicrobial activity directly when used in food products and in active food packaging, or indirectly when used as sanitizing or antibiofilm agents on food-and other contact surfaces (Pedonese et al, 2017).…”
Section: Strategies Using Natural Compoundsmentioning
confidence: 99%